2020
DOI: 10.1097/jxx.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient access through office hysteroscopy clinic redesign

Abstract: Background and objective: Patients with abnormal uterine bleeding (AUB) often require hysteroscopy as part of the diagnostic workup. The purpose of this study was to improve efficiency by shortening the time to patient appointment for office hysteroscopy. Interventions: Preintervention, nurse practitioners (NPs) and gynecologists saw patients with abnormal uterine bleeding (AUB) separately. This created inefficiency for the patients, frequently requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Collectively, these studies suggested that 68%–89% of patients were evaluated and managed in the first one‐stop clinic visit. A collaborative hysteroscopy clinic with women's health nurse and gynecologist improved service “availability” by increasing the number of appointment slots by more than 50% and reducing the waiting time for appointments 12 . A prospective study, that interviewed 22 women with AUB, confirmed that a one‐stop clinic was suited to the needs of these women 16 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Collectively, these studies suggested that 68%–89% of patients were evaluated and managed in the first one‐stop clinic visit. A collaborative hysteroscopy clinic with women's health nurse and gynecologist improved service “availability” by increasing the number of appointment slots by more than 50% and reducing the waiting time for appointments 12 . A prospective study, that interviewed 22 women with AUB, confirmed that a one‐stop clinic was suited to the needs of these women 16 .…”
Section: Resultsmentioning
confidence: 98%
“…Following title screening, we included 314 records, which was reduced to 91 after abstract screening. After full‐text screening, 21 papers 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 were included. Two papers 29 , 30 were from one study, so the total number of included studies was 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 205 patients with abnormal uterine bleeding admitted to hospital from February 2020 to February 2022 were selected as experimental subjects, and the patients were aged from 30 to 65 years old. According to the corresponding diagnostic criteria of endometrial polyp, endometrial hyperplasia, and endometrial cancer [ 13 , 14 ], 205 patients were divided into the endometrial polyp group (56 cases), endometrial hyperplasia and canceration group (84 cases), and normal cycle endometrial group (65 cases). General data of patients were collected, and related factors were analyzed.…”
Section: Methodsmentioning
confidence: 99%